ANALISIS PERSEPSI PETANI TERHADAP PEMANFAATAN BOKASHI PADA PERTANAMAN PADI SAWAH - Basri, Hasan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
The purpose of this study is to analyze the implementation level of introduce technology of bokashi on rice cultivation. This study was conducted in the village Kuripan Sub Penengahan, South Lampung regency. Technique of data collecting conducted by field observation and interview by using of quizioner. Determine of sample conducted with purposive sampling. Data analysed using non parametric analysis (rating scale). Result of the study relevead that the public interest of farmer very high to bokashi applying. Based to result of evaluation about perception of farmer to technology of making and applying of bokashi in rice cultivation, applying has 72,0% high respons and 28,0% do not respons.